LEGAL PROTECTION AGAINST LAND BUYER IN GOOD INDENCE IN LAND OWNERSHIP (World Bulletin of Management and Law, 2023)
Legal protection for a good faith land buyer in a land dispute is absolutely given as long as the buyer has done the things that have been stipulated in the laws and regulations before buying and selling land. The method used in this research is normative legal research which is carried out as an effort to obtain the necessary data related to the problem. The results of the study state that the law provides for buyers who carry out sales and purchases that meet the clear and cash requirements in the transition, namely buying and selling before the PPAT or the village head. The buyer must conduct research on the land he is going to buy and the buyer must be careful before buying and selling land